2008
DOI: 10.3354/meps07232
|View full text |Cite
|
Sign up to set email alerts
|

Parasite-associated mortality of juvenile Pacific salmon caused by the trematode Nanophyetus salmincola during early marine residence

Abstract: The potential effect of the freshwater trematode Nanophyetus salmincola on early marine survival of Pacific salmon was assessed by monitoring the prevalence and intensity of metacercarial infection in yearling coho salmon Oncorhynchus kisutch, and yearling and subyearling Chinook salmon O. tshawytscha caught off Oregon and Washington during May, June, and September of 1999 to 2002. Annual prevalences of N. salmincola infection in yearling coho salmon were 62 to 78% and were significantly greater each year than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 29 publications
0
50
0
Order By: Relevance
“…The majority of data presented here for N. salmincola from 1999 to 2002 are from Jacobson et al . (). Some additional archived samples from 2003 to 2004 were also analysed for this study.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…The majority of data presented here for N. salmincola from 1999 to 2002 are from Jacobson et al . (). Some additional archived samples from 2003 to 2004 were also analysed for this study.…”
Section: Methodsmentioning
confidence: 97%
“…Several studies have demonstrated the ability of N. salmincola to increase mortality in infected juvenile salmonids (Baldwin, Milleman & Knapp ; Butler & Milleman ; Newcomb, Snell & Waknitz ; Jacobson et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…owing to the trematode Nonophyetus salmincola [58]. However, none of the above example studies of parasiterelated mortality have been able to establish if parasitism is linked with declines in host fish recruitment, or is otherwise offset by compensatory mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Metacercariae most often cause disease in fish only in heavy infections, 37 and mortality associated with N. salmincola in salmon is correlated with intensity of infection. 12,20,25 It would therefore be unlikely that missing these light infections by histology would have compromised diagnoses for cause of morbidity. Although some light infections appeared to only be detected by wet mount, several infections were detected by histology and not this method.…”
Section: Discussionmentioning
confidence: 99%